Lithology, stratigraphy, chemostratigraphy, and depositional environment of the Mississippian Sycamore rock in the SCOOP and STACK area, Oklahoma, USA: Field, lab, and machine learning studies on outcrops and subsurface wells. (May 2020) - Milad, Benmadi; Slatt, Roger; Fuge, Zou
Abstract: This paper presents an interpreted depositional environment, developed 2nd order sequence stratigraphy framework, and detailed lithofacies identification from two Mississippian Sycamore outcrops (I-35 Sycamore and Speake Ranch) and subsurface wells in the SCOOP (South Central Oklahoma Oil Province). Then these rocks calibrate the rock properties with wireline log responses to identify the best landing zones. Qualitative and quantitative techniques of field, laboratory, and machine learning studies were conducted. For the field studies, we measured the complete 450 ft of the outcrop stratigraphic section, another separate 50 ft outcrop, examined the underlying Woodford Shale and overlying Caney Shale boundary contacts, documented sedimentary structures, constructed an outcrop gamma-ray profile, and developed a sequence stratigraphic framework. Laboratory studies included petrographic analyses, detailed X-ray Fluorescence (XRF), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD). For machine learning studies, a principal component analysis (PCA), elbow method, and self-organizing map (SOM) were used to analyze the electrofacies and chemofacies from the outcrop and a subsurface uncored well. The outcrop hand-held gamma ray profile was obtained and correlated with subsurface wells. Five major outcrop lithofacies and chemofacies, within six stratigraphic units of alternating siltstone and shale strata, were identified from the wireline logs. A Maximum Flooding Surface (MFS), and two major 2nd order Sequence Boundaries (SB) were recognized at the outcrop and a nearby subsurface well. Bouma sequences and repetitive cycles of sedimentary structures indicated sediment gravity flow deposition on a marine slope setting. This study provides geologic insights to better understanding the depositional environment and the lithology of the Sycamore rocks. The bioturbated siliceous shale and/or the sandy siltstone can be potential target zones due to their reservoir quality, lithology, bed continuity, and brittleness. This information can be of direct benefit to the exploration and development programs of many companies in the SCOOP area, particularly in the Anadarko and Ardmore basins in Oklahoma. Highlights: Outcrop studies converted into digital data for subsurface geological assessments of Mississippian Sycamore. This study integrates detailed field descriptions, lithology, electrofacies, fracture, chemo and sequence stratigraphy. The outcrop studies are correlated to regional subsurface cross section SCOOP area. I-35 Sycamore outcrop findings used to the subsurface predictions for the enhancement of exploration and development programs. Results highlight possible target lithology for drilling. Mississippian Sycamore was deposited in a quiet, deep marine environment by gravity flow deposit/turbidity currents.